Point-prevalence survey of carbapenemase-producing Enterobacteriaceae and vancomycin-resistant enterococci in adult inpatients in a university teaching hospital in the UK. Issue 1 (September 2018) - Wilson, H.J.; Khokhar, F.; Enoch, D.A.; Brown, N.M.; Ahluwalia, J.; Dougan, G.; Török, M.E.
Summary: Infections with carbapenemase-producing Enterobacteriaceae (CPE) and vancomycin-resistant enterococci (VRE) are associated with increased morbidity and mortality, but the carriage rates of CRE and VRE among hospital inpatients are unknown. A point-prevalence survey was conducted to determine CPE and VRE carriage rates in hospitalized adults. Eight hundred and eighteen of 960 (85.2%) adult inpatients were invited to participate in the study. Of these, 595 patients (72.7%) consented and provided specimens. Of 540 samples tested, none were positive for CPE. One hundred and thirty of 540 (24.1%) samples were VRE positive, and 34 of 40 (85%) of wards had cases. Universal screening for CPE may not be cost-effective in low-prevalence settings, but targeted screening of high-risk patients should continue. The optimal screening strategy for VRE remains to be determined, as universal screening and isolation is not feasible in the study setting.